Pinay power peminist critical theory: theorizing the Filipina/American experience - De Jesus, Melinda L. 1965- (New York Routledge, 2005)
"Pinay Power: Peminist Critical Theory is a collection of peminist (Filipina American feminist) cultural criticism by and about Filipina Americans. It features essays by female scholars and writers who tackle issues such as gender, decolonization, globalization, transnationalism, identity, sexuality, representation and spirituality. It also features examples of peminist artwork."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Critical theory; Feminism -- United States; Feminist theory -- United States; Filipino American women -- Intellectual life; Filipino American women -- Social conditions